How Do Companies Respond to Environmental, Social and Governance (ESG) ratings? Evidence from Italy - Clementino, Ester; Perkins, Richard (Journal of business ethics, 2021)
While a growing number of firms are being evaluated on environment, social and governance (ESG) criteria by sustainability rating agencies (SRAs), comparatively little is known about companies' responses. Drawing on semi-structured interviews with companies operating in Italy, the present paper seeks to narrow this gap in current understanding by examining how firms react to ESG ratings, and the factors influencing their response. Unique to the literature, we show that firms may react very differently to being rated, with our analysis yielding a fourfold typology of corporate responses. The typology captures conformity and resistance to ratings across two dimensions of firm behaviour. We furthermore show that corporate responses depend on managers' beliefs regarding the material benefits of adjusting to and scoring well on ESG ratings and their alignment with corporate strategy. In doing so, we challenge the idea that organisational ratings homogenise organisations and draw attention to the agency underlying corporate responses. Our findings also contribute to debates about the impact of ESG ratings, calling into question claims about their positive influence on companies' sustainability performance. We conclude by discussing the wider empirical, theoretical and ethical implications of our paper.